A brief neuro-affirming resource to support school absences for autistic learners: development and program description - Johnston, Lorna; Maciver, Donald; Rutherford, Marion; Gray, Anna; Curnow, Eleanor; Utley, Izy (Frontiers in Education, 2024)
Education should be inclusive, nurturing each individual's potential, talents, and creativity. However, criticisms have emerged regarding support for autistic learners, particularly in addressing disproportionately high absence levels within this group. The demand for accessible, person-centred, neuro-affirming approaches is evident. This paper provides a programme description of a structured absence support framework, developed and implemented during and following the Covid-19 pandemic. We detail creation, content, and implementation.We collaborated with stakeholders, reviewed literature and drew on existing theoretical frameworks to understand absence in autistic learners, and produced draft guidance detailing practical approaches and strategies for supporting their return to school. The final resource was disseminated nationally and made freely available online with a supporting programme of work around inclusive practices.The resource is rooted in neuro-affirming perspectives, rejecting prevailing sanction or reward-based systems and deficit models of autism. It includes key messages, case studies and a planning framework. It aims to cultivate inclusive practices with an autism-informed lens. The principles promoted include recognising the child's 24-hour needspresentation, parental partnership, prioritising environmental modifications, and providing predictable, desirable and meaningful experiences at school. Feedback to date has been positive in terms of feasibility, face validity, and utility.This novel, freely available resource provides a concise, practical framework for addressing absence in autistic learners by cultivating a more inclusive, equitable, and supportive educational system in which autistic individuals can thrive.